The Use of Illustrators by Bahdini Kurdish Teachers in EFL University Classrooms - Fakhir Omar Mohammed; Sazan Abbas Saidgul; Bokan Ghazi Khalid (Zanco Journal of Humanity Sciences)
This study investigates the various kinds of illustrators that male and female Bahdini Kurdish (BK) lecturers perform in EFL university classes. In this area of study, there is still a lack of research on the impact of nonverbal cues on university-level teaching and learning processes when it comes to classroom communication between instructors and students. Ten university instructors, both male and female, were chosen as a sample for the study. Data was gathered from the lecturers using a descriptive observation method based on the illustrator classification system developed by Ekman and Friesen (1969, 1972). According to the results obtained from using excel sheets, the majority of lecturers employed deictic movements in their classes, followed by kinetographs and spatial movements. In terms of gender, females made up a large share of illustrators, except for ideographs.